Kelas Sosial adalah Segalanya: Bagaimana Penonton Indonesia Memaknai Film "Crazy Rich Asian"? - M Raihan Taruna; Ratna Permata Sari (Jurnal Mahasiswa Komunikasi Cantrik, 2022)
This study will focus on social class reception analysis in the film “Crazy Rich Asians”. The Crazy Rich Asians film, which was released in 2018, tells the story of Rachel Chu's love story with Nick Young which is opposed by Nick's mother because of Rachel's different social class background. Therefore, due to the various social class differences in Indonesia, the researcher will analyze the film using the Stuart Hall reception analysis method which focuses on differences in social class in the fields of Culture, Education, Wealth and Work. This study took five informants who have different cultural backgrounds. The supporting theories in this research are Fiske's theory of film representation as social reality and Karl Marx's theory of social class. The results of this study found that social class and social stratification that occurred in Indonesia were very diverse and adjusted to the area of ​​each informant. From the results of research on the analysis of social class receptions in the film "Crazy Rich Asians". In the dominant position of hegemony, the majority of informants agreed that the difference in social class is true when it comes to (1) Marriage culture which is attended by family and does not elope. (2) educational background. (3) Wealth and family background. In the opposition position, the majority of informants contradict the concept of being picky about the background of their potential partner when they get married. In a negotiating position, informants who are in this stage find it difficult to make decisions in matters relating to the cultural background of the prospective partner and the background of the position. Based on the results of in-depth interviews with the five married informants and watching the Crazy Rich Asians film, it can be found that the differences in reception results that occur come from cultural factors, wealth, education and work of each informant.